The River Basin Principle of Water Resources Management in the Legislation of the European Union and Ukraine - Danyliuk, Lesia (Journal of Vasyl Stefanyk Precarpathian National University, 2018)
The article studies the notion of the river basin principle of water resources management, its meaning, its legal definition in the EU directives, the particular aspects of its implementation in Ukraine, and its overall importance in terms of water quality and management of water resources, including the marine environment. It is determined that the river basin principle of water resources management is one of the key matters of the EU environmental policy and is a topical issue for Ukraine in the process of European integration. Essentially, the river basin principle of water resources management is defined as integrated management within a river basin district. It is concluded that this principle is one of the main components of integrated management of water resources and is, in fact, the basis of the integrated approach to such management.